SAT0559 Reuma.Pt/LES: the Experience of Two Central Hospitals in Lisbon. (23rd January 2014) - Sousa, S. I.; Gonçalves, M. J.; Roque, R.; Vinagre, F.; Cordeiro, A.; Godinho, F.; Saavedra, M. J.; Ramos, F.; Macieira, C.; Canhão, H.; Fonseca, J. E.; da Silva, C.; et al.
Abstract : Background: Reuma.pt, the Rheumatic Diseases Register from the Portuguese Society of Rheumatology has recently expanded its coverage to Systemic Lupus Erythematous (SLE) patients, the Reuma.pt/LES. Reuma.pt/LES is a web-based platform launched in September 2012 that simultaneously serves as a nationwide registry and as an electronic medical record. Its aim is to register all patients with SLE and follow them up in a standard manner in order to improve the monitoring and clinical care for patients with SLE while simultaneously increase the knowledge of this disease. Methods: The authors present the structure and the functioning of this national project, giving as an example the subpopulation of patients with SLE from two centres in Lisbon (Hospital Santa Maria and Hospital Garcia de Orta) included in Reuma.pt/LES. Results: 878 patients from all the country with the clinical diagnosis of SLE were registered in the database Reuma.pt/LES until January 2013. Recorded information includes demographics, work status, life-styles, ACR and SLICC 2012 classification criteria, thrombotic and obstetric manifestations, SLE disease activity at each visit, fatigue scale, health related quality of life measures (SF-36 and EQD5), irreversible damage, comorbid conditions, medication and adverse events. Hospital Santa Maria (Lisbon) and the Hospital Garcia de Orta (Almada) contributed to Reuma.pt/LES with 305 patients, 95, 1% females, 80% Caucasians with a mean age of 45.5 ±14.9y. The mean age at diagnosis was 35.9 ±14.9y and the mean disease duration was 10.3 ± 7.3y. SLE Disease Activity Index (SLEDAI) at the first evaluation was 3, 4 ± 3, 8 and current accrual damage assessed by the Systemic Lupus International Collaborating Clinics (SLICC) was 0, 7 ± 1, 1. Hypertension was reported in 24% of the patients, diabetes in 8.8% and cardiovascular diseases in 11%. The vast majority of patients was treated with hydroxychloroquine (93.9%) and corticosteroids (prednisolone 44.6%, prednisone 12.4%, deflazacort 18.%). Immunosuppressive drugs were used in about half of the cases (azathioprine in 27%, methotrexate in 15.5%, cyclophosphamide in 7.4%, micophenolate in 5%) and to a lesser extent biological therapies (rituximab in 5.9% and belimumab in 0.98% of the patients). Conclusions: Reuma.pt, is a very useful tool, that allows a more efficient patient follow-up, and standardized data collection, storage and analysis, with the ultimate objective of improving patient care and simultaneously scientific research in the field of SLE. Disclosure of Interest: None Declared